2004
DOI: 10.1212/wnl.62.6_suppl_4.s32
|View full text |Cite
|
Sign up to set email alerts
|

Practical considerations in the use of apomorphine injectable

Abstract: This manuscript provides a practical summary of guidelines for institution of apomorphine subcutaneous injectable therapy, including patient education, pre-treatment issues, dosage titration and side-effect care. The timing of each injection is crucial if an impending "off" period is to be averted. Patients need to be aware of symptoms of an approaching "off" period, and the injection should be administered at the onset or ideally, in anticipation of an "off" episode. Patients being considered for apomorphine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 23 publications
1
29
0
4
Order By: Relevance
“…Changing the site of injection every day and careful local hygiene reduce the incidence and severity of such a reaction. [219,220] Application-site reactions were cited as the most common adverse reaction to transdermal rotigotine in RCTs. [85,87,115,116] The majority of these events were rated as mild to moderate and appeared to be dose related.…”
Section: Non-dopaminergic Adverse Reactionsmentioning
confidence: 99%
“…Changing the site of injection every day and careful local hygiene reduce the incidence and severity of such a reaction. [219,220] Application-site reactions were cited as the most common adverse reaction to transdermal rotigotine in RCTs. [85,87,115,116] The majority of these events were rated as mild to moderate and appeared to be dose related.…”
Section: Non-dopaminergic Adverse Reactionsmentioning
confidence: 99%
“…Trials have also been conducted using the anti-emetic trimethobenzamide, which works directly on the chemoreceptor trigger zone in the periphery. This drug is largely an anti-histamine with low affinities for dopamine receptors thus producing antiemetic effects without antidopaminergic properties [26]. The majority of the therapeutic trials conducted in the late 1980s and 1990s consistently demonstrated a reduction in the number of daily 'off' periods [4,25,[27][28][29][30][31].…”
Section: Early Clinical Data In Pdmentioning
confidence: 99%
“…45 A Coombs test should be performed beforehand to exclude circulating antibodies against erythrocytes. One of the main side effects is skin reactions, located at the injection side, resulting in the formation of small nodules.…”
Section: Ossig and Reichmannmentioning
confidence: 99%